A comparative study to induce Growth Hormone with insulin and Exercise in patients with short stature aged 6-12 years in Tishreen Hospital. (Latakia University Journal -Medical Sciences Series, 2018)
Objective: Comparison the quality of the physical Exercise versus the Insulin as GH provocation tests by comparing the average of the GH excretion peaks after provocation , Studying the relationship between the time of the blood sample and the GH secretory and determination the best time , Studying the relationship between serum sugar values ​​and GH values, The Side effects. Methods: The study sample included 60 patients in Tishreen University Hospital in Lattakia during (2016 - 2017) with a Short stature and ages ranging 6-12 years. The GH provocation was performed for 30 patients with insulin, and 30 patients with physical Exercise. Venous blood samples were withdrawn at 5 times (0, 30, 60, 90, 120) minutes after provocation , with clinical monitoring of the patient in the hospital for 4 hours after the provocation test. Results: The GH provocation with insulin showed GH peaks (9.07 ± 0.80) ng / ml versus (4.23 ± 0.36) ng / mL after physical Exercise with p-value = 0.0001. Therefore, the Statistical significance is for insulin provocation, and the relationship between sampling time and GH- Insulin provocation showed that the value of GH for the first time was the best with p-value = 0.006, and there was no relationship after the physical Exercise provocation test . The Side effects after insulin provocation were demonstrated in 5 patients and were tolerated by them, absent after Exercise provocation test , but insulin provocation test remains the best.. دراسة مقارنة لتحريض هرمون النمو بالأنسولين و الجهد الفيزيائي عند مرضى قصر القامة بين عمر 6-12 سنة بمشفى تشرين الجامعي. هدف الدراسة: دراسة فعالية التحريض بالجهد الفيزيائي على ذرا GH عن طريق مقارنة متوسط القمم الإفرازية ل GH بعد اختباري التحريض بالجهد الفيزيائي والأنسولين، دراسة العلاقة بين زمن أخذ العينة الدموية و القمة الإفرازية ل GH وتعيين أفضل زمن، دراسة العلاقة بين قيم سكر الدم و القيم الموافقة ل GH، الآثار الجانبية للعامل المحرض. طريقة البحث والمرضى:شملت عينة الدراسة 60 مريضاً متتابعاً من الأطفال المراجعين إلى مشفى تشرين الجامعي في اللاذقية خلال الفترة (2016 -2017) م بقصة قصر قامة وتراوحت الأعمار بين 6-12 سنة، حيث تم إجراء تحريض GH ل 30 مريضاً بالأنسولين، مقابل 30 مريضاً بالجهد الفيزيائي. تم أخذ عينات دموية وريدية ب 5 أزمنة (0، 30، 60، 90، 120) دقيقة بعد التحريض، مع المراقبة السريرية للمريض بالمشفى لمدة 4 ساعات بعد إجراء اختبار التحريض. النتائج:أبدى التحريض بالأنسولين ذرا GH (9.07±0.80) نانوغرام/مل مقابل (4.23±0.36) نانوغرام/مل بعد التحريض بالجهد الفيزيائي مع p-value=0.0001 بالتالي وجود أهمية احصائية لصالح التحريض بالأنسولين، وبدراسة علاقة زمن أخذ العينة والقمة الافرازية لـGH بعد التحريض بالأنسولين تبين أن قيمة GH للزمن الأول هو الأفضل مع p-value=0.006 ، ولم يكن هناك علاقة بعد تحريض الجهد الفيزيائي. تظاهرت الآثار الجانبية بعد التحريض بالأنسولين عند 5 مرضى وكانت متحملة من قبلهم وغائبة بعد التحريض بالجهد الفيزيائي، لكن يبقى التحريض بالأنسولين هو الأفضل.